A Meta-Analytic Assessment of the Effect of Immigration on Wages - Simonetta Longhi; Peter Nijkamp; Jacques Poot (Tinbergen Institute, 2004)
In our increasingly interconnected and open world, international migration is becoming an important socio-economic phenomenon for many countries. Since the early 1980s, many studies have been undertaken of the impact of immigration on host labour markets. Borjas (2003) noted that the estimated effect of immigration on the wage of native workers varies widely from study to study and sometimes even within the same study. In addition, these effects cluster around zero. Such a small effect is a rather surprising outcome, given that in a closed competitive labour market an increase in labour supply may be expected to exert a downward pressure on wages. We revisit this issue by applying meta-analytic techniques to a sample of eighteen papers_new, which altogether generated 348 estimates of the percentage change in the wage of a native worker with respect to a one percentage point increase in the ratio of immigrants over native workers. While many studies in our sample employ US data, estimates are also obtained from Germany, The Netherlands, France, Norway, Austria, Israel and Australia. Our analysis shows that results vary across countries and are inter alia related to the type of modelling approach. Technical issues such as publication bias and quality of the estimates are addressed as well. A negative but small effect of immigration on wages of native groups with similar skills appears rather robust.
Keywords: C51; F22; J31; J61; 330; Immigration; Labour market; Factor substitution; Meta-analysis; Einwanderung; Arbeitsmarkt; Lohn; Faktorsubstitution